Cerebellar Abscess Mimicking Recurrent Pilocytic Astrocytoma: A Case Report - Devkota, Harihar; Jha, Rajiv (Nepal Journal of Neuroscience, 2016)
Cerebellar abscess is a rare condition occurring more commonly in children and adolescents usually caused by otitis media. They can occur following trauma or surgery or from septic focus directly or hematologically. It is sometime hard to distinguish from other space occupying lesion clinically or by imaging modalities. We report a case of an eight year boy who had undergone craniotomy and excision of a pilocytic astrocytoma two years back and now presented with headache and preoperative diagnosis of recurrent pilocytic astrocytoma was made. But, to our surprise, the operative findings showed an abscess which was confirmed with histopathology. The final diagnosis of cerebellar abscess was made. Nepal Journal of Neuroscience 12:85-87, 2015